Nocturnal frontal lobe epilepsy presenting as sleepwalking episodes and restless leg syndrome-like symptoms - Arya Jith; Kathleen Anne Mathew; Kudrat Jain (Annals of Indian Psychiatry, 2022)
Nocturnal frontal lobe epilepsy (NFLE) is characterized by seizures with complex motor behaviors arising mainly during sleep. Varied clinical presentations and nonspecific electroencephalogram findings make it difficult to distinguish NFLE from other nocturnal paroxysmal events such as nonrapid eye movement (NREM) parasomnias and restless leg syndrome (RLS). Here, we present a case of NFLE, which had a complex clinical presentation resembling features suggestive of RLS and NREM parasomnia and posed a diagnostic challenge. Initiation of carbamazepine as the anti-epileptic led to rapid resolution of symptoms.